Implementation Of Decision Support System Topsis Fuzzy MCDM Method For Web-Based Cafe Recommendation - Kholis, Mukhamad Jainur; Dr. Istiadi S.T.,M.T.; Aviv Yuniar Rahman, S.T., M.T (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2024)
The purpose of this research is to provide recommendations for cafes using the TOPSIS Fuzzy MCDM method and implementing it in a web-based system. This system aims to assist consumers in choosing a cafe based on various factors such as location, facilities, rating, price, and service quality. The TOPSIS Fuzzy MCDM method was selected for its ability to handle uncertainty and produce a more accurate ranking of alternatives. The research demonstrates that this system can deliver recommendations aligned with predetermined preferences, thereby facilitating better decision-making. The study was conducted by researchers in the Malang City area, but the system is accessible to users from any location based on their coordinates. The test results show that the system successfully provides recommendations with scores of 100%, 73.07%, 53.92%, and so forth. These findings indicate that the system can effectively help users decide on their preferred cafe by offering reliable and accurate recommendations. Moreover, the integration of real-time data and Google Maps ensures that the recommendations are up-to-date and relevant. This implementation is expected to enhance the consumer decision-making process, providing a practical tool for selecting cafes that meet specific user criteria. This research underscores the potential of using advanced decision-making methods like TOPSIS Fuzzy MCDM in real-world applications, demonstrating its effectiveness in improving the user experience in the cafe selection process. The system's capability to integrate additional information, such as social media presence and customer reviews, could further enhance its utility in future developments.